Supply Chain Risk Management of The Small-Scale Industry in West Sumatera - Yuni Ernita; Rika Ampuh Hadi Guna; Santosa Santosa; Nofialdi Nofialdi (School of Business, Bogor Agricultural University (SB-IPB), 2018)
The existing cacao industry in West Sumatera is a small scale cacao industry. One of the risks encountered in this industry is that the production does not meet the target and the specification set, resulting in the difficulties for the industry to develop. The objective of the research is to conduct a supply chain risk management in the small scale cacao industry in West Sumatera. . This research used a survey approach method. While the data collected were primary and secondary data. The supply chain management process used descriptive method and Analytic Network Process (ANP). Study on cacao industry chain supply risk source showed indicates that production risks are in the highest priority with a value of 21.78%. The marketing, financial, institutional and human resource risks have the same priority risk i.e. 19.55%. The highest priority of risk types includes the risk of availability of industrial capital, government policy, skills and personal knowledge, and production process cost, with the priority values of 0.102634; 0.101024; 0.099903; and 0.041294 respectively. An alternative risk control priority is to weaken risk (0.39191), and risk segregation (0.25798). Supply chain risk management needs to be held by weakening and segregating risks through improving product management, supply management and information management prioritized on procurement and production processes, thereby enhancing the quality and quantity of processed cocoa products on an ongoing basis. The results of the study can become an input to stakeholders related to the development of small-scale cocoa industry in West Sumatera.